Empathy and humanitarianism predict preferential moral responsiveness to in-groups and out-groups. Issue 6 (2nd November 2018) - Redford, Liz; Ratliff, Kate A.
ABSTRACT: The current research tests whether empathy—sharing others' emotions—and humanitarianism—recognizing the moral worth of all people—each predict moral responsiveness toward others but in ways that favor in-groups and out-groups, respectively. In Studies 1 and 2, empathy and humanitarianism differentially predicted preferential moral concern for in-groups and out-groups. In Study 3, humanitarianism predicted lower in-group-targeted prosociality and greater out-group prosociality. In Study 4, empathy and humanitarianism predicted perceived moral obligation to in-groups and out-groups respectively. In Study 5, out-group obligation mediated between humanitarianism and allocations to out-group charities, and in-group obligation mediated between empathy and one of two in-group charities. In sum, empathy and humanitarianism are associated with preferential morality via group-based obligation, suggesting that morality could be extended by altering empathy, humanitarianism, or group processes.